Design and Evaluation of Solid Lipid Nanoparticles of an Antibiotic-mannitol as Cryoprotectant - Chandira, Rajappa Margret; Pethappachetty, Palanisamy; Lakhshmanan, Gokulnath; samy, Dominic Antony (Asian Journal of Biological and Life Sciences)
Mannitol was used as a cryoprotactant to freeze-dry Doxycycline nanoparticles for colloidal drug administration in this work. in this research, the benefits include Medicines like vaccines and other injectables, which have a short shelf life and are commonly freeze-dried to increase their shelf life. A liquid may be treated more easily with aseptic handling because of this. The stability of a dry powder has been increased. In addition, water may be removed from the device without causing it to overheat. Reconstituted product dissolves quickly and readily. All of these concerns are avoided so that the product may be transported or stored at room temperature without suffering deterioration or degradation due to aggregation. Preparation of doxycycline SLNs included homogenization and sonication. Antimicrobial activity and in vitro anticancer activity are among the techniques employed in this investigation. Freeze drying was also a component of the process, as was particle size, drug loading, and drug release. The lipid solid’s particle size distribution At various magnifications of the investigation, nanoparticles are determined to be 3.66, 6.58, 9.96, 4.97, 17.36, and 25.48mm in diameter. A freeze-dryer was used to freeze-dry the particles at -20°C and 0.4 pressure. Mannitol at various concentrations (5, 10, and 15 percent) was utilised as a cryoprotectant. Drug loading was determined to be 78 percent, while drug release was found to be 98 percent after 24 hr. Maximum inhibition of cell growth (69.9422) was seen at an IC50 concentration of 100g/mL of leaf crude extract (48.69g/mL). Doxycycline SLNs might be inferred to be more stable, less aggregate, and have fewer adverse effects when freeze-dried.
Keywords: Activity; Doxycycline; Freeze-drying; Solid lipid nanoparticles; Stability